Giving beyond the gift : apophasis and overcoming theomania - Wolfson, Elliot R. (Fordham University Press, 2014)
This book explores the co-dependency of monotheism and idolatry by examining the thought of several prominent twentieth-century Jewish philosophers Cohen, Buber, Rosenzweig, and Levinas. While all of these thinkers were keenly aware of the pitfalls of scriptural theism, to differing degrees they each succumbed to the temptation to personify transcendence, even as they tried either to circumvent or to restrain it by apophatically purging kataphatic descriptions of the deity. Derrida and Wyschogrod, by contrast, carried the project of denegation one step further, embarking on a path that culmina.